Parity in the German Labour Market Nearly Achieved - Alexander Kubis (Wirtschaftsdienst)
Abstract With 1.9 million vacancies available to 2.3 million registered unemployed persons, parity in the German labour market has almost been achieved. Such parity however may produce labour shortages that go far beyond small bottlenecks, which are limited to particular regions and industries. In the short term, labour demand may be curtailed by temporary risks such as an energy crisis. In the medium term however, projections indicate that demographic change will significantly reduce the labour supply. Maintaining the current high level of economic activity therefore requires an all-out effort to raise the potential supply of skilled workers. (Re-)training and further education are but two elements of such an effort that work by also reducing the skill-based mismatch that has risen from ecological and technological change.